PELATIHAN STRATEGI PEMASARAN PRODUK VCO DAN TURUNANNYA DI IKM RUMAH IKHTIAR - Rosdiani Azis (UPPM Politeknik Gorontalo, 2021)
IKM Rumah Ikhtiar is an IKM that is engaged in coconut processing, especially the processing of VCO and its derivative products. The huge marketing potential of VCO, the demand for charcoal, and the use of ethanol as an ingredient for making hand sanitizers during the pandemic show that this IKM-processed product is quite important. However, currently production is carried out based on customer orders only. This causes the income every month to be erratic and even non-existent. Therefore, the service team agreed to make improvements in the marketing field. Marketing is done by utilizing social media (Facebook) and online stores such as Shopee. Marketing by utilizing digital technology requires training from competent experts, so the service team conducts marketing management training in the form of rapid technology guidance (Bimtek) for 1 day. The activity was attended by 7 members of IKM, a team of service people and resource persons who are experts in the field of marketing. The results achieved from this training include: a sales account on Facebook and a shopee account under the name IKM Rumah Ikhtiar, IKM members are proficient in marketing on Facebook and Shopee and sales for 1 week after marketing using Facebook and Shopee has increased compared to before. Previously, VCO sales were only 2 liters per week, after using a marketing strategy with Facebook and Shopee, sales increased to 6-10 liters per week.